NEED FOR APPLICATION OF BLENDED LEARNING ACCORDING TO (HE) TEACHERS AND STUDENTS IN SOCIAL SCIENCES - Butrimė, Edita; Zuzevičiūtė, Vaiva; Jarmakovienė, Justina (Acta Paedagogica Vilnensia, 2009)
Contemporary higher education is changing under the influence of many factors, among which the advancement of technologies has an important role. Due to this advancement, both traditional teaching / learning, and the studies that are incorporating e-learning elements, are being implemented. Studies that incorporate e-learning (distance learning) elements are called blended learning. Researchers in the field provide arguments that blended learning complements the most advantageous characteristics of both traditional and distance learning in studies. However, in Lithuania there are not many studies in the field, and especially with the focus on whether teachers and students in higher education find blended learning acceptable. In the first part of the paper discussions on the contents and the scope of blended learning are provided. In the second part the needs of teachers (in HE), who try to integrate e-learning (distance) into their teaching, are analysed. The third part describes the needs of students who experience or try to implement technologies in their studies to a greater extent. Lastly, the fourth part of the paper presents the results of the empiric research. The empiric research was carried out in 2008, the method of interview was employed. It was aimed at identifying the needs of teachers who have experience in implementing e-learning elements in traditional studies (i.e., implement blended learning). It was also aimed at identifying the students who have experience in blended learning. Both teachers and students represented the sphere of social sciences rather than information sciences, where such experience is more common. Results of the analysis of interviews revealed that the teachers need to have a challenge in their work and in order to implement blended learning they need professional development in the field of technologies, they also need to feel support for blended learning and to meet the needs and expectations of their students. The study also revealed that students among the other needs mentioned the need to acquire additional skills that are crucially important in blended learning, namely, time management.
Keywords: blended learning; needs of teachers; needs of students